A Review of Phosphide-Based Materials for Electrocatalytic Hydrogen Evolution - Xiao, Peng (2017)
Hydrogen evolution by means of electrocatalytic water-splitting is pivotal for efficient and economical production of hydrogen, which relies on the development of inexpensive, highly active catalysts. In addition to sulfides, the search for non-noble metal catalysts has been mainly directed at phosphides due to the superb activity of phosphides for hydrogen evolution reaction (HER) and their low-cost considering the abundance of the non-noble constituents of phosphides. Here, recent research focusing on phosphides is summarized based on their synthetic methodology. A comparative study of the catalytic activity of different phosphides towards HER is then conducted. The catalytic activity is evaluated by overpotentials at fixed current density, Tafel slope, turnover frequency, and the Gibbs free energy of hydrogen adsorption. Based on the methods discussed, perspectives for the various methods of phosphides synthesis are given, and the origins of the high activity and the role of phosphorus on the improved activity towards HER are discussed.